Increased Activity Tolerance based on Hemodynamic Status in Patients Coronary Heart Disease After Physical Rehabilitation of Phase I (Inpatient) - Wiwiek Retti Andriani; Endang Purwaningsih (Universitas Muhammadiyah Semarang, 2020)
Coronary Heart Disease (CHD) is caused by atheroma/plaque attached to the endothelial lining of the coronary arteries which causes blockages in oxygen and nutrient distribution to the tissues. This condition causes CHD patients to experience deficits in functional capacities, such as self-care ability, incapacity for performing the activity of daily living and also social activities. This study aims to analyze activity tolerance based on hemodynamic status (respiration, blood pressure, pulse frequency, oxygen saturation) in CHD patients after phase 1 physical rehabilitation (inpatient). The research method is quasy experiment one group pre-post-test research method. The results of data analysis using the Friedman test found that there was a significant effect on respiration on days 2, 3, systolic blood pressure on days 1 and 3, no significant effect on diastolic blood pressure, significant changes in oxygen saturation on days 1, 2, and 3, changes in pulse frequency on days 1 and 3.